Gestión del Talento Humano en el Comercial “Angelito” de la ciudad de Vinces. - Jonathan Josué, Rodríguez Villavicencio (2017)
LEl Comercial "Angelito", is a service company more assortment of the city of Vinces; whose economic activity is the commercialization of national and imported products, of coast and mountain range that is dedicated to the sale of inputs, dairy products, meat, canned goods, liqueurs, cigarettes, glassware, confectionery, school supplies and articles of bazaar, beverages and soft drinks wholesale, and everything related to household consumption